2007
DOI: 10.1111/j.1442-2018.2007.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

The expertise of Finnish occupational health nurses

Abstract: This study describes the self-assessed activities, features, prerequisites, and consequences of occupational health nurses' expertise. The quantitative data were gathered from 468 Finnish occupational health nurses, of whom 373 (80%) returned the completed questionnaire. The data were analyzed by using one-way-anova, the Kruskal-Wallis or the chi(2)-tests. The activities of the occupational health nurses included working with employees, workplaces, and collaborative partners, administrative and office work, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The articles in the sample, not least those with a nursing perspective, first and foremost included the principles ‘empowerment’ (11, 16–20, 22, 29) and ‘participation’. In many papers, the latter was replaced by expressions such as ‘(inter)relationship’ (15, 21, 22, 29), ‘partnership’ (16, 28), ‘interaction’ (11, 20, 25) and ‘collaboration’ (12, 17, 19, 25), or by wordings such as ‘a nurse–patient relationship characterised by equality’ (15: 389). Most articles with an entire or combined health promotion/nursing perspective also included ‘intersectoral collaboration’, primarily with specialists (12, 19, 25) and various sectors from the local community (11, 14, 16, 27–29, 32).…”
Section: Resultsmentioning
confidence: 99%
“…The articles in the sample, not least those with a nursing perspective, first and foremost included the principles ‘empowerment’ (11, 16–20, 22, 29) and ‘participation’. In many papers, the latter was replaced by expressions such as ‘(inter)relationship’ (15, 21, 22, 29), ‘partnership’ (16, 28), ‘interaction’ (11, 20, 25) and ‘collaboration’ (12, 17, 19, 25), or by wordings such as ‘a nurse–patient relationship characterised by equality’ (15: 389). Most articles with an entire or combined health promotion/nursing perspective also included ‘intersectoral collaboration’, primarily with specialists (12, 19, 25) and various sectors from the local community (11, 14, 16, 27–29, 32).…”
Section: Resultsmentioning
confidence: 99%
“…No data were presented to substantiate such an exaggerated claim. In a somewhat larger survey, the same author found that the unique characteristics of occupational health nurses were their "holistic perspective and listening to clients" and the main benefits of their expertise were "improved health and a decreased number of work-related health risks" [152]. In articles such as these, occupational health nurses advocate international expansion of their field, without first obtaining the scientific knowledge and professional attributes required to advance occupational health and effectively prevent occupational disease.…”
Section: International Expansion Of Occupational Nursingmentioning
confidence: 99%